Efficacy and safety of canagliflozin over 52 weeks in patients with type 2 diabetes on background metformin and pioglitazone. Issue 5 (12th March 2014) - Forst, T.; Guthrie, R.; Goldenberg, R.; Yee, J.; Vijapurkar, U.; Meininger, G.; Stein, P.
Abstract Aim The efficacy and safety of canagliflozin, a sodium glucose co‐transporter 2 inhibitor, was evaluated in patients with type 2 diabetes mellitus (T2DM) inadequately controlled with metformin and pioglitazone. Methods In this randomized, double‐blind, phase 3 study, patients (N = 342) received canagliflozin 100 or 300 mg during a 26‐week, placebo‐controlled, core period and a 26‐week, active‐controlled extension in which placebo‐treated patients were switched to sitagliptin 100 mg. Efficacy comparisons for canagliflozin versus placebo at week 26 are reported, with no comparisons versus sitagliptin at week 52 (sitagliptin used to maintain double‐blind and control for safety). Safety data are reported for canagliflozin and placebo/sitagliptin. Results Canagliflozin 100 and 300 mg significantly lowered haemoglobin A1c (HbA1c) compared with placebo at week 26 (−0.89%, −1.03% and −0.26%; p < 0.001); reductions with canagliflozin 100 and 300 mg were maintained at week 52 (−0.92% and −1.03%). Relative to placebo, both canagliflozin doses significantly reduced body weight (−2.5 and −3.5 kg), fasting plasma glucose and systolic blood pressure (BP) at week 26 (p < 0.05 for all), with reductions maintained at week 52. Overall adverse event (AE) incidence over 52 weeks was 69.9, 76.3 and 76.5% with canagliflozin 100 and 300 mg and placebo/sitagliptin; AE‐related discontinuation and serious AE rates were low. Incidences of genital mycotic infections and AEs related to osmotic diuresis and volume depletion were higher with canagliflozin than placebo/sitagliptin. Conclusion Canagliflozin improved glycaemic control, reduced body weight and systolic BP, and was generally well tolerated in patients with T2DM on metformin and pioglitazone over 52 weeks.